Pengaruh Digital Marketing, Harga Dan Kualitas Pelayanan Terhadap Volume Penjualan Pada Cafe Goodbeb Di Pariaman - Meidona, Syofria; Asrul, Asrul; Putri, Yesi Loveran (LPPM Universitas Dharma Andalas, 2025)
This research aims to determine the influence of digital marketing, price and service quality on sales volume at Cafe Goodbeb in Pariaman. Quantitative research is a valid and reliable instrument as well as appropriate analysis so that it does not deviate from actual conditions and research by obtaining data in the form of numbers. The population in this research is all consumers who have visited or shopped at Cafe Goodbeb, the number of which is unknown. The sample in this study was 68 respondents . Data was collected using a questionnaire and analyzed using the SPSS version 23 for Windows program. Based on the results obtained, the multiple linear regression value is Y=7.777+ 0.113X1 + 0.585X2+ 0.250X3. . Then the results. First Hypothesis Test (H1) H1: Digital Marketing. t calculated has a value of 3.949. Meanwhile, the t table in this study has a value of 1.99773, this shows that the calculated t value > t table (3.949 > 1.99773) which means that Digital Marketing has a significant and influential effect on sales volume. Second Hypothesis Test (H2) H2: The calculated t price has a value of 10.416. Meanwhile, the t table in this study has a value of 1.99773. which means that price has a significant and influential effect on sales volume. Third Hypothesis Test (H3) H3: Service Quality. t count has a value of 6.166. Meanwhile, the t table in this study has a value of 1.99773. which means that service quality has a positive and significant effect on sales volume. f count is 94,900. Meanwhile, the f table in this study has a value of 2.75. This means that the calculated f value is greater than the f table (94,900 > 2.75). Meanwhile, judging from the significance value of 0.000, the significance value is smaller than 0.05. The coefficient of determination value is 0.808. This means that 80.8% of sales volume is influenced by digital marketing, price and service quality. Meanwhile, the remaining 19.2% of sales volume is influenced by other variables not examined in this research.